Teaching Father-Infant Massage during Postpartum Hospitalization: A Randomized Crossover Trial. Issue 3 (May 2020) - Suchy, Carol; Morgan, Gloria; Duncan, Susan; Villar, Susan; Fox, Frieda; Rutledge, Dana N.
Abstract: Purpose: The purpose of this study was to evaluate acceptability and impact of infant massage video instruction on fathers' behaviors in early postpartum. Methods: A randomized crossover design was used. Participants were fathers of healthy term infants born at a Magnet hospital in Southern California. Measures included a demographic survey, Father-to-Infant Bonding Scale, Father-Infant Observation Scale, and postdischarge phone interview. Study nurses observed father–infant interactions for 5 minutes. Fathers were randomized to one of two groups: fathers in group 1 saw the massage video before they were observed with their infants and fathers in group 2 saw the video after. Fathers completed the Bonding Scale at baseline in person and again within a week of discharge by phone. Statistics were descriptive and comparative. Responses to interview questions were categorized and described. Results: Ninety-eight fathers aged 18 to 44 years participated. Over half of fathers identified as Hispanic and the majority spoke English at home. Most fathers had positive responses to infants on individual Bonding Scale items. Fathers differed significantly in observed interactions with infants depending upon timing of massage instruction; fathers observed immediately after the video had more total interactions, specifically fingertip touching. Poststudy evaluations were predominantly positive. Clinical Implications: We found a brief infant massage instruction offered by video was well accepted by fathers and increased observed father–infant interactions. Abstract : In this randomized crossover trial, new fathers were randomized to viewing a video about infant massage before or after they were observed by nurses during father-infant interactions. Fathers who had viewed the massage video had increased bonding interactions compared with fathers who had not seen the video. Fathers were positive about learning infant massage. Newborn massage by fathers may be one way to enhance paternal bonding.